Intramuscular ganglion of gastrocnemius muscle-unusual presentation of a common tumour - Zachariah, Sanoop Koshy; Ajay, Gayathri; Mathews, Kocheril Sheryl; Thomas, John (International Surgery Journal, 2017)
Ganglion cysts (GCs) are one of the most common benign cystic lesions that commonly arise from joints of the wrist. The diagnosis is usually straightforward in these situations. Nevertheless, they have been reported to rarely arise in certain unusual anatomic locations leading to diagnostic difficulties. Here we report an atypical presentation of a ganglion cyst within the gastrocnemius muscle. To the best of our knowledge this is the second case of histologically proven intramuscular ganglion cyst presenting within the gastrocnemius muscle, to be reported in literature.